SELF-ACCEPTANCE OF PEOPLE LIVING WITH HIV/AIDS (PLWHA) EX FEMALE SEX WORKER (FSW) - Alvian Pristy Windiramadhan (JURNAL KESEHATAN INDRA HUSADA, 2021)
Background: HIV / AIDS is a disease where the incidence rate is still very high globally and still cannot be cured. So that self-acceptance of people living with HIV / AIDS or known as PLWHA is not an easy thing. Purpose: The purpose of this study was to reveal in depth the self-acceptance of PLWHA ex-FSW. Methods: The research design used was qualitative with a descriptive phenomenology approach. Data were collected by in-depth interviews with six PLWHA ex-FSW who has disclosed the status and condition of the disease to health workers. The research results were analyzed using the Colaizzi method. Results: All participants in this study were PLWHA ex-FSW who had worked as FSW for 2-6 years, the age range of participants was between 25-38 years and their last education was elementary school. Based on the Results are described in three related themes i.e.: 1) Felt the inner pressure when you know that you are HIV positive, 2) Motivated yourself and getting support from the closest people, and 3) Accepted and opened up their status as ODHA. Conclusion: The process of self-acceptance of PLWHA, former FSW is not an easy thing, so it needs support from the closest people and health workers.